Visual Feedback Attenuates Mean Concentric Barbell Velocity Loss and Improves Motivation, Competitiveness, and Perceived Workload in Male Adolescent Athletes. Issue 9 (September 2019) - Weakley, Jonathon J.S.; Wilson, Kyle M.; Till, Kevin; Read, Dale B.; Darrall-Jones, Joshua; Roe, Gregory A.B.; Phibbs, Padraic J.; Jones, Ben
Abstract : Abstract: Weakley, JJS, Wilson, KM, Till, K, Read, DB, Darrall-Jones, J, Roe, GAB, Phibbs, PJ, and Jones, B. Visual feedback attenuates mean concentric barbell velocity loss and improves motivation, competitiveness, and perceived workload in male adolescent athletes. J Strength Cond Res 33(9): 2420–2425, 2019—It is unknown whether instantaneous visual feedback of resistance training outcomes can enhance barbell velocity in younger athletes. Therefore, the purpose of this study was to quantify the effects of visual feedback on mean concentric barbell velocity in the back squat and to identify changes in motivation, competitiveness, and perceived workload. In a randomized-crossover design (Feedback vs. Control), feedback of mean concentric barbell velocity was or was not provided throughout a set of 10 repetitions in the barbell back squat. Magnitude-based inferences were used to assess changes between conditions, with almost certainly greater differences in mean concentric velocity between the Feedback (0.70 ± 0.04 m·s −1 ) and Control (0.65 ± 0.05 m·s −1 ) observed. In addition, individual repetition mean concentric velocity ranged from possibly (repetition number 2: 0.79 ± 0.04 vs. 0.78 ± 0.04 m·s −1 ) to almost certainly (repetition number 10: 0.58 ± 0.05 vs. 0.49 ± 0.05 m·s −1 ) greater when provided feedback, whereas almost certain differences were observed in motivation, competitiveness, and perceived workload, respectively. Providing adolescent male athletes with visual kinematic information while completing resistance training is beneficial for the maintenance of barbell velocity during a training set, potentially enhancing physical performance. Moreover, these improvements were observed alongside increases in motivation, competitiveness, and perceived workload providing insight into the underlying mechanisms responsible for the performance gains observed. Given the observed maintenance of barbell velocity during a training set, practitioners can use this technique to manipulate training outcomes during resistance training.